2016
DOI: 10.3389/fphys.2016.00643
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Different Exercise Protocols on the Circulating Vascular microRNAs -16, -21, and -126 in Trained Subjects

Abstract: Aim: mircoRNAs (miRNAs), small non-coding RNAs regulating gene expression, are stably secreted into the blood and circulating miRNAs (c-miRNAs) may play an important role in cell–cell communication. Furthermore, c-miRNAs might serve as novel biomarkers of the current vascular cell status. Here, we examined how the levels of three vascular c-miRNAs (c-miR-16, c-miR-21, c-miR-126) are acutely affected by different exercise intensities and volumes.Methods: 12 subjects performed 3 different endurance exercise prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 50 publications
(79 reference statements)
5
39
0
Order By: Relevance
“…Their results suggest that exercise can also improve miR-126 levels in the circulation. In vitro findings have suggested that miR-126 is mainly of endothelial origin [38]. In addition, Wang et al [39] found that miR-126 overexpression significantly increased EPC colony formation, proliferation, and migration and reduc apoptosis in patients with diabetic vascular disease when compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggest that exercise can also improve miR-126 levels in the circulation. In vitro findings have suggested that miR-126 is mainly of endothelial origin [38]. In addition, Wang et al [39] found that miR-126 overexpression significantly increased EPC colony formation, proliferation, and migration and reduc apoptosis in patients with diabetic vascular disease when compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Of these genes, there is much evidence that SPRED1 is a target of miR‐126 in promoting angiogenesis . Interestingly, recent studies have not only revealed important roles for miR‐126 in response to cardiac ischaemia, but have also demonstrated that exercise up‐regulates miR‐126 expression . Accordingly, we speculated that miR‐126 may up‐regulate exercise‐induced EPC function in mice after MI.…”
Section: Introductionmentioning
confidence: 99%
“…; Wahl et al. ) and longer exercise training interventions (Taurino et al. ; Van Craenenbroeck et al.…”
Section: Discussionmentioning
confidence: 99%